Penerapan UI/UX Jahit Buk Las di Kota Pekanbaru Menggunakan Metode Lean UX: Jahit Buk Las di Kota Pekanbaru - Iyan, Julian Nanda Mardiwanto; Rizki, Muhammad; Eiva Fathda, Syarifah (Fakultas Ilmu Komputer Universitas Almuslim Bireuen - Aceh, 2023)
Sewing is the work of joining cloth, fur, animal skin, pepagan, and other materials that can be used with a sewing needle and thread. Sewing can be done by hand using a hand needle or with a sewing machine. People who work sewing clothes are called tailors. Men's clothing tailors are called tailors, while women's clothing tailors are called modiste. The community felt the impact of the government's implementation and restrictions, namely difficulty meeting needs that had to be done in person, so they had to move online. However, there were also many things that made sewing services less popular with the public before the pandemic, namely various things, namely unknown or far locations, less extensive orders that only consisted of local people, sewing not according to consumers' wishes and long sewing times. To overcome this problem, a mobile application is needed to help the community, so a solution is needed to help connect tailors and the wider community as potential customers. To realize this solution, researchers propose a sewing application solution design to help people find tailors according to their wishes and needs. The lean UX method is a method that changes a long process into a short one that has success and a very fast process and focuses on increasing user understanding of the design being designed. This application will make it easier for users to place orders on the Buk Las Sewing Application.